2019
DOI: 10.1002/pc.25211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low concentration hollow glass microspheres on mechanical and thermomechanical properties of epoxy composites

Abstract: The processing of hollow glass microsphere (HGM) based composites is one of the growing areas in materials research due to the potential of significantly changing material properties even at low HGM concentrations. HGM-epoxy composites are prepared by sonication method. Four weight ratio configurations are considered (1, 3, 5 wt% HGM and 5 wt% NH 2 functionalized HGM) and compared with neat epoxy to study the microenrichment effect. The influence of low volume HGM and functionalized HGM reinforcement on epoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The syntactic foam exhibits some improved reliability to mechanical and electrical loading when compared with the mere resin formed products. Also properties can be tailored as per the demand by varying the proportion of HGM and selecting appropriate wall thickness to a considerable extent [1][2][3][4][5][6][7]. Among other hollow micro spheres HGM possess significant lower density, higher thermal insulation and high dielectric constant [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The syntactic foam exhibits some improved reliability to mechanical and electrical loading when compared with the mere resin formed products. Also properties can be tailored as per the demand by varying the proportion of HGM and selecting appropriate wall thickness to a considerable extent [1][2][3][4][5][6][7]. Among other hollow micro spheres HGM possess significant lower density, higher thermal insulation and high dielectric constant [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the glass transition temperature (T g ) of syntactic foam increases [1] and coefficient of thermal expansion (CTE) reduces when compared to epoxy as HGM restricts polymer chain mobility caused due to increase in temperature, which proves to be a significant contribution in thermal stability. [6] Introduction of hollow microspheres reduces the epoxy volume fraction and increases the inhomogeneity content, consequently reducing the tensile strength of the composite. Epoxy volume fraction and effective tensile strength of the composite decrease due to increase in HGM volume because of poor interfacial strength between the matrix material and HGM; however, its specific strength (strength per unit density) increases due to the lower density of HGM.…”
Section: Introductionmentioning
confidence: 99%
“…Koopman et al explored the compression of glass micro balloons and observed a clear correlation between the diameter to failure load and diameter to fracture energy [10]. Mohammed Imran et al studied the variable weight percentage of HGM in epoxy composites made by the sonication method and reported that the compressive strength declined when the HGM weight percentage increased and the storage modulus increased [11]. Rahaman et al investigated the glass fiber-reinforced laminated epoxy carbon nano tube composites and discovered that the addition of multi-walled carbon nano tubes significantly enhanced the composite's flexural modulus, flexural strength, and modulus of storage [12].…”
Section: Introductionmentioning
confidence: 99%